Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada PT. Trans Sumatera Agung Gatot Subroto Medan - Nizamuddin Nizamuddin (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
Trans Sumatera Agung Gatot Subroto Medan is one of Suzuki's showrooms that sells four-wheeled vehicles and is located on Gatot Subroto Street in Medan. The challenges faced include intense competition among several showrooms on Gatot Subroto Street, low visitor turnout, and the quality of products and services provided. This research aims to determine the influence of Product Quality, Service Quality, and Price on Customer Satisfaction at PT. Trans Sumatera Agung Gatot Subroto Medan. Data collection was done by distributing questionnaires to 80 respondents. The results of this study show that Product Quality, partially, does not have a significant effect, while Service Quality and Price, partially, have a significant effect on Customer Satisfaction. Product Quality, Service Quality, and Price, collectively, significantly influence Customer Satisfaction. The Adjusted R Square is 0.747 or 74.7%, meaning that Product Quality, Service Quality, and Price account for 74.7%, and the remaining percentage is explained by other factors.